2017
DOI: 10.1007/s10295-017-1903-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduced production of diacetyl by overexpressing BDH2 gene and ILV5 gene in yeast of the lager brewers with one ILV2 allelic gene deleted

Abstract: Diacetyl causes an unwanted buttery off-flavor in lager beer. The production of diacetyl is reduced by modifying the metabolic pathway of yeast in the beer fermentation process. In this study, BDH2 and ILV5 genes, coding diacetyl reductase and acetohydroxy acid reductoisomerase, respectively, were expressed using a PGK1 promoter in Saccharomyces cerevisiae, which deleted one ILV2 allelic gene. Diacetyl contents and fermentation performances were examined and compared. Results showed that the diacetyl content i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…However, superior results have been obtained using recombinant strains with a deletion of ILV2 and simultaneously overexpressing ILV5. This research regarding flavor volatile compounds biosynthesis pathways might be relevant for future beer off-flavor control studies or to identify bacterial spoilage during the brewing process [79,80,81].…”
Section: Complementary Beer Volatile Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, superior results have been obtained using recombinant strains with a deletion of ILV2 and simultaneously overexpressing ILV5. This research regarding flavor volatile compounds biosynthesis pathways might be relevant for future beer off-flavor control studies or to identify bacterial spoilage during the brewing process [79,80,81].…”
Section: Complementary Beer Volatile Compoundsmentioning
confidence: 99%
“…Phenolic compounds, such as hydroxycinnamic acids ( p -coumaric acid and isoferulic acid) and flavan-3-ols (catechins and epicatechins), in malt and beer have a strong impact on antioxidant activity (increased shelf-life) and colloidal stability (foam and haze) of beer. Polyphenolic compounds in beer are mainly derived from malt (75%) and hop (25%) and they are claimed to be one of the major sources of beer antioxidants [80,83,87]. Cheiran et al (2019) studies identified fifty-seven phenolic compounds by HPLC-DAD-ESI-MS/MS measurements, and 12 of these compounds had never been previously identified in beer [82].…”
Section: Beer Phenolic Compounds Profilementioning
confidence: 99%
“…Moreover, the acetohydroxyacid reductoisomerase (Ilv5p) catalyzes the degradation of α-acetolactate to produce dihydroxy isovalerate, hence the content of diacetyl is also regulated by Ilv5p (Omura, 2008;van Bergen et al, 2016;Shi et al, 2017). In our study, the diacetyl content of strains overexpressing the ILV2 gene was only slightly increased, which may be related to the decomposition of a part of α-acetolactate by Ilv5p.…”
Section: No Influence Of Ilv2 Overexpression On Production Of Ttmp Inmentioning
confidence: 56%
“…Shi et al (2016) reduced the diacetyl content during beer fermentation by 17.83% by knocking out the ILV2 gene in brewer's yeast strain. Meanwhile, the content of diacetyl was decreased by 61.93% in recombinant brewer's yeast, which deleting ILV2 gene and overexpressing acetohydroxyacid reductoisomerase encoding gene ILV5 (Shi et al, 2017). These results indicated that the expression of ILV2 gene is related to diacetyl biosynthesis.…”
Section: No Influence Of Ilv2 Overexpression On Production Of Ttmp Inmentioning
confidence: 83%
“…A number of strategies are used, or have been proposed, for diacetyl control [ 26 ]. Genetic modification of yeast for lowered acetohydroxy acid synthase activity, increased acetohydroxy acid reductoisomerase activity, increased diacetyl reductase activity [ 11 , 30 , 34 , 40 ], or expression of foreign α-acetolactate decarboxylase [ 6 ], has been shown to be effective, but is not feasible due to current restrictions on the use of GM technology in food production. α-Acetolactate production varies with yeast strain, and strain selection is a simple strategy for diacetyl control [ 18 ].…”
Section: Introductionmentioning
confidence: 99%